Improved Access and Participation for Persons with Disabilities in Local Governance - Sonia Fontanilla -Pimentel (Indonesian Association for Public Administration, 2020)
The disability agenda has only gained adequate attention in the public administration discourse after the United Nations (UN) Convention on the Rights of PWDs (CRPD) was enacted on 13 December 2006, followed by the launching of the Sustainable Development Goals (SDGs) in 2015 which included Goal No. 3 on Good Health and Well Being, and Goal No. 10 on Reduced Inequalities. In the Philippines, Republic Act 7277 known as the Magna Carta for Disabled Persons and Republic Act 10070 which provided for the creation of Persons with Disabilities Affairs Office (PDAO) in local government units are among the laws currently governing disability affairs matters. This paper looks into the status of the implementation of RA 10070 in the Provincial Government of Camarines Norte, Philippines. The researcher used qualitative methodology including key informants’ interview, focus group discussion case analysis and documentary analysis. The paper ends by the establishment of a framework, the Disability-Inclusive Theory or ACCESS Theory, that discusses the conditions and elements affecting the formulation of policies and enactment of local laws that provide access and other means to eventually empower PWDs and enable them to become more active participants in their respective communities.